Assessing Water Resource Planning Policies in the Sefidroud Irrigation and Drainage Network Using the Water-Land-Food Nexus Approach - S. Ashkevari; S. Janatrostami; A. Ashrafzadeh (علوم آب و خاک)
In this study, a conceptual model based on dynamic systems was developed to optimize the management of water, land, and agricultural production (tea and rice) in the irrigation zones of the Sefidroud irrigation and drainage network. To understand the behavior of the network and create a simulation model of the system, a dynamic systems modeling approach was employed, and the simulation was conducted using MATLAB/Simulink. Subsequently, the optimization model of the studied system was developed as a multi-objective model using a genetic algorithm. Various management scenarios were implemented through the weighting of the objective functions. The results showed that selecting the best response from multi-objective optimization models depends on the weighted values of the objective functions, and by changing these values, decision-makers can provide various responses to complex optimization problems. The optimization model determines the cultivated area and water allocation in such a way as to minimize water scarcity and maximize crop performance through different weighting combinations. Furthermore, the findings indicate that the canals of the irrigation network play a crucial role in meeting water needs, and equitable water allocation is essential to prevent excessive extraction and negative consequences, such as saline intrusion and land subsidence. The study demonstrates that the best solutions are contingent upon local conditions and decision-makers' policies. To achieve maximum economic benefits and address water needs, it is suggested to use a weighting combination close to (w1=1,w2=2). Ultimately, this model assists managers and decision-makers in minimizing water scarcity in the region by adjusting cropping levels and optimizing the use of available water resources.